2021
DOI: 10.14309/crj.0000000000000702
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatitis A and Hepatitis B Coinfection

Abstract: Hepatitis A (HAV) has emerged in outbreaks across the United States particularly in at-risk populations such as men who have sex with men, as well as patients with a history of drug use, homelessness, and incarceration. Immunization among these high-risk populations remains underused. In this study, we describe a case of acute HAV and hepatitis B (HBV) coinfection in an MSM patient occurring in the period of these outbreaks. Clinical resolution of acute HAV and HBV coinfection was attained by 5 months from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Positive autoimmune antibodies, such as rheumatoid factor (RF), can result in a false-positive IgM HAV test result. Negative anti-HAV IgG or negative HAV RNA confirms the false-positive condition in this instance [ 1 3 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Positive autoimmune antibodies, such as rheumatoid factor (RF), can result in a false-positive IgM HAV test result. Negative anti-HAV IgG or negative HAV RNA confirms the false-positive condition in this instance [ 1 3 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 79%
“…Even though hepatitis A and B are vaccinepreventable diseases, recent studies in the United States indicate an increase in the incidence of HAV infection between 2016 and 2018, with admission and mortality rates of 67% and 2.7%, respectively. In addition, HBV estimated acute infections remained stable from 2016 to 2019; it was 20,700 patients in 2019, and the prevalence of chronic HBV infection was estimated at 1.59 million patients in the same year [1][2][3]7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study found that while over half of injection drug users tested positive for anti-HAV total antibody, none of them tested positive for anti-HAV immunoglobulin M (IgM), indicating that none had acute infection with HAV [ 11 ]. There have only been two other case reports of acute co-infection with HAV and HBV in general [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%